Potential influences of complement factor H in autoimmune inflammatory and thrombotic disorders. (April 2017) - Ferluga, Janez; Kouser, Lubna; Murugaiah, Valarmathy; Sim, Robert B.; Kishore, Uday
Highlights: Factor H is important for complement system homeostasis, host self-protection and anti-microbial immune surveillance. Its deficiency or mutations have been linked with familial and sporadic autoimmune inflammatory–thrombotic disorders, in which autoantibodies play a substantial part. The diseases include systemic lupus erythematosus, rheumatoid arthritis, atypical haemolytic uremic syndrome, and anti-phospholipid syndrome. There are overlaps in the pathology and autoantibodies. Underlying events seem to be a decline in peripheral regulatory T cells, dendritic cell, and B cell tolerance, associated with alterations in lymphoid organ microenvironment. Factor H also contributes to self-tolerance. Factor H is able to discriminate between self-antigens and bacterial antigens for self-protection and anti-microbe defence. Factor H may potentially inhibit blood coagulation; through its platelet receptor, factor H may have an anti-thrombotic role. Abstract: Complement system homeostasis is important for host self-protection and anti-microbial immune surveillance, and recent research indicates roles in tissue development and remodelling. Complement also appears to have several points of interaction with the blood coagulation system. Deficiency and altered function due to gene mutations and polymorphisms in complement effectors and regulators, including Factor H, have been associated with familial and sporadic autoimmune inflammatory − thrombotic disorders, in which autoantibodies play a part. These include systemic lupus erythematosus, rheumatoid arthritis, atypical haemolytic uremic syndrome, anti-phospholipid syndrome and age-related macular degeneration. Such diseases are generally complex − multigenic and heterogeneous in their symptoms and predisposition/susceptibility. They usually need to be triggered by vascular trauma, drugs or infection and non-complement genetic factors also play a part. Underlying events seem to include decline in peripheral regulatory T cells, dendritic cell, and B cell tolerance, associated with alterations in lymphoid organ microenvironment. Factor H is an abundant protein, synthesised in many cell types, and its reported binding to many different ligands, even if not of high affinity, may influence a large number of molecular interactions, together with the accepted role of Factor H within the complement system. Factor H is involved in mesenchymal stem cell mediated tolerance and also contributes to self-tolerance by augmenting iC3b production and opsonisation of apoptotic cells for their silent dendritic cell engulfment via complement receptor CR3, which mediates anti-inflammatory-tolerogenic effects in the apoptotic cell context. There may be co-operation with other phagocytic receptors, such as complement C1q receptors, and the Tim glycoprotein family, which specifically bind phosphatidylserine expressed on the apoptotic cell surface. Factor H is able to discriminate between self and nonself surfaces for self-protection and anti-microbe defence. Factor H, particularly as an abundant platelet protein, may also modulate blood coagulation, having an anti-thrombotic role. Here, we review a number of interaction pathways in coagulation and in immunity, together with associated diseases, and indicate where Factor H may be expected to exert an influence, based on reports of the diversity of ligands for Factor H.